The unseen effect of pesticides: The impact on phytobiota structure and functions - Sangiorgio, Daniela; Spinelli, Francesco; Vandelle, Elodie (Frontiers in Agronomy, 2022)
In the last years, the diffusion and implementation of next-generation sequencing and the reduction of costs raised the interest in phytyobiome studies allowing to dissect the ecological interactions regulating the holobiont. Indeed, crop plants are associated with a wide diversity of microorganisms in all their parts. Crop microbiota influences plant phenotype, growth, yield and quality by contributing to plant resistance toward diseases, plant adaptation to abiotic stresses, and plant nutrition. The association between terrestrial plants and microbes developed at least 460 million years ago, as suggested by the fossil evidence of the earliest land plants, indicating the essential role of microbes for plants. Recent studies indicate that plants actively recruit beneficial microorganisms to facilitate their adaptation to environmental conditions. Cultivation methods and disease control measures can influence plant microbiome structure and functions. Both pesticide and biological control agent applications may alter the biodiversity inside the phytobiota and suppress beneficial functions. Nonetheless, to date, the effects of disease control measures on phytobiota and their possible side consequences on plant growth, crop productivity and quality remain a neglected field of study. The present work summarizes the known effects on phytobiota providing evidence about the role of plant microbial community in determining the overall efficacy of the applied control measure and suggests that future studies on plant disease control consider also the microbe-mediated effects on plant fitness.